2022
DOI: 10.3390/healthcare10061018
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Pandemic-Revealed Consistencies and Inconsistencies in Healthcare: A Medical and Organizational View

Abstract: The circumstances of the Coronavirus disease caused by the SARS-CoV-2 virus (COVID-19) pandemic have had a significant impact on global and national developments, affecting the existence of society in all its expressions, as well as the lives of people themselves. In the context of the pandemic, increased attention has been focused on acute measures, but the ending of the pandemic is expected as a resolution of the related healthcare problems. However, there are several indicators that the COVID-19 pandemic mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 73 publications
0
14
0
2
Order By: Relevance
“…However, in recent years, natural disasters caused by climate change and various epidemics have exerted a great impact on global development, and have also sent a warning to human society to achieve the United Nations 2030 Sustainable Development Goals (SDGs) as scheduled [ 2 ]. In particular, COVID-19, which has killed millions of people across 215 countries, poses a huge threat to the health of people around the world [ 3 , 4 , 5 ]. The impact of the COVID-19 on the economic order and social activities has been unprecedented.…”
Section: Introductionmentioning
confidence: 99%
“…However, in recent years, natural disasters caused by climate change and various epidemics have exerted a great impact on global development, and have also sent a warning to human society to achieve the United Nations 2030 Sustainable Development Goals (SDGs) as scheduled [ 2 ]. In particular, COVID-19, which has killed millions of people across 215 countries, poses a huge threat to the health of people around the world [ 3 , 4 , 5 ]. The impact of the COVID-19 on the economic order and social activities has been unprecedented.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is correct to state that the area of afference of the physicians and dentists included in this study had one of the highest rates of diffusion and severity of COVID-19. The excess mortality could also have been influenced by the overload of the healthcare system, [ 36 , 50 ] which could have led to a reduction in the level of care for both patients with COVID-19 and those with other acute or chronic diseases [ 9 , 51 , 52 , 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…The authors, in one of the previous studies on the COVID-19 pandemic consistencies in healthcare [3], revealed that since October 2020, several articles have reported myalgic encephalomyelitis/chronic fatigue syndrome (ME/CFS) as a potentially post-COVID-19-associated disease [4][5][6][7][8][9][10][11]. The literature reviews on the potential causal interaction between post-COVID-19 and ME/CFS also appeared in the following period [12][13][14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%